Pericytes in the infarcted heart - Alex, Linda (Vasc Biol, 2019)
The adult mammalian heart lacks regenerative capacity and heals through activation of an inflammatory cascade that leads to the formation of a collagen-based scar. Although scar formation is important to preserve the structural integrity of the ventricle, unrestrained inflammation and excessive fibrosis have been implicated in the pathogenesis of adverse post-infarction remodeling and heart failure. Interstitial cells play a crucial role in the regulation of cardiac repair. Although recent studies have explored the role of fibroblasts and immune cells, the cardiac pericytes have been largely ignored by investigators interested in myocardial biology. This review manuscript discusses the role of pericytes in the regulation of inflammation, fibrosis and angiogenesis following myocardial infarction. During the inflammatory phase of infarct healing, pericytes may regulate microvascular permeability and may play an important role in leukocyte trafficking. Moreover, pericyte activation through Toll-like receptor-mediated pathways may stimulate cytokine and chemokine synthesis. During the proliferative phase, pericytes may be involved in angiogenesis and fibrosis. To what extent pericyte to fibroblast conversion and pericyte-mediated growth factor synthesis contribute to the myocardial fibrotic response remains unknown. During the maturation phase of infarct healing, coating of infarct neovessels with pericytes plays an important role in scar stabilization. Implementation of therapeutic approaches targeting pericytes in the infarcted and remodeling heart remains challenging, due to the lack of systematic characterization of myocardial pericytes, their phenotypic heterogeneity and the limited knowledge on their functional role.